Preparation method and application of molecular sieve-based honeycomb denitration catalyst taking FCC (fluid catalytic cracking) waste catalyst as carrier
By pretreating the FCC waste catalyst and combining it with components such as molecular sieve-based catalysts, a highly active and economical production molecular sieve-based honeycomb denitrification catalyst is prepared, which solves the problem of low utilization efficiency of FCC waste catalysts in the prior art, and achieves an efficient and environmentally friendly nitrogen oxide removal effect.
Patent Information
- Application Number
- CN202411531008.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-30
AI Technical Summary
The prior art is difficult to effectively utilize FCC waste catalysts as support to prepare highly active and economically produced molecular sieve-based honeycomb denitrification catalysts, especially in maintaining the catalytic activity of molecular sieve and achieving smooth molding.
By pretreating the FCC waste catalyst, including roasting, acid etching and crushing, and then dry mixing, kneading and extruding with components such as molecular sieve-based catalyst, structural manufacturing agent and binder, the structure adjustment is performed using water-soluble polymer fibers to form a molecular sieve-based honeycomb denitrification catalyst with the FCC waste catalyst as the support.
The effective recycling of FCC waste catalysts is achieved, the activity and accessibility of the catalysts are improved, the hole blockage phenomenon caused by the addition of the molecular sieve catalysts is avoided, and the cost of solid waste treatment and catalyst preparation is reduced, and the cost of good industrial application is provided.
Smart Images

Figure BDA0005110470000000081 
Figure BDA0005110470000000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nitrogen oxide removal, and specifically relates to a preparation method and application of a molecular sieve-based honeycomb denitration catalyst using an FCC waste catalyst as a carrier. Background Art
[0002] Nitrogen oxides (NO x ) is one of the main air pollutants, which is extremely harmful to human body, environment and even social economy. Among the many denitrification technologies, selective catalytic reduction (NH 3 -SCR) technology is the most mature and widely used. The vanadium element in the traditional vanadium-tungsten-titanium catalyst is biologically toxic and environmentally harmful, while the molecular sieve catalyst has the characteristics of special pore structure, adjustable acidity and excellent hydrothermal stability, and has a good performance in the removal of nitrogen oxides, so it can be used as a core catalyst; on the other hand, TiO 2 As the main catalytic carrier is expensive, it is particularly important to find a catalytic carrier that is compatible with the molecular sieve catalyst.
[0003] FCC catalysts are widely used in oil processing. About 200,000 tons of FCC catalysts are put into production in my country every year, of which about 150,000 tons of solid waste are discharged, and a lot of resources are needed to treat them. FCC waste catalysts are mainly Y-type molecular sieves, kaolin and related binders, and contain a certain amount of rare earth elements such as La and Ce, and inorganic elements such as Ni, V, and Fe. Kaolin has a certain promoting effect in catalyst molding. In addition, some elements can help remove nitrogen oxides. Therefore, it is considered that it can be used as a honeycomb integral denitrification catalyst carrier after processing.
[0004] Chinese patent application CN 115672262 A combines FCC waste catalyst with clay to form an adsorbent, confirming that the pre-treated FCC waste catalyst has the possibility of further utilization. Chinese patent application CN109985670 A combines waste honeycomb TiO 2 Combined with FCC waste catalyst, a denitrification catalytic carrier is prepared, which does not contain catalytic active components and does not consider the adjustment of the structure and pores inside the carrier. Chinese patent application CN 116689018 A uses FCC waste catalyst as the main component to prepare a carrier, and after a certain acid treatment, in-situ growth of CeO 2 and La 2 O 3This technology improves the roughness of the surface after molding, promotes surface growth, and improves the catalytic performance to a certain extent. Chinese patent application CN 109482222B successfully prepared a honeycomb denitrification catalyst through pretreatment technology. This technology uses metal oxides such as V as the main active components and still has certain biological toxicity. Although the recovery and treatment technology of FCC waste catalysts has been reported, there is a certain gap in the extrusion technology combined with molecular sieve catalysts. The biggest difficulty is how to use FCC waste catalysts as carriers without reducing the catalytic activity of the molecular sieve and achieving the purpose of smooth molding. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a molecular sieve-based honeycomb denitrification catalyst using FCC waste catalyst as a carrier and its application. The present invention utilizes FCC waste catalyst as a resource, realizes the preparation of a honeycomb monolithic catalyst while treating solid waste, and structurally adjusts the catalyst to increase the accessibility of catalyst activity.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing a molecular sieve-based honeycomb denitration catalyst using FCC waste catalyst as a carrier comprises the following steps:
[0008] (1) The FCC waste catalyst is calcined to remove organic matter, crushed, etched with acid solution, filtered, dried, calcined, and crushed to obtain pretreated FCC waste catalyst powder;
[0009] (2) Pre-treated FCC waste catalyst powder, molecular sieve-based catalyst, structure-making agent, organic binder, inorganic binder, pore-forming agent, extrusion aid, glass fiber, acid solution, moisturizing agent and water are taken, and dry-mixed, kneaded, slurried, aged, extruded, pre-dried, structured water-soluble, dried and calcined to obtain a molecular sieve-based honeycomb denitrification catalyst with FCC waste catalyst as carrier, which can be applied to NH 3 -SCR reaction.
[0010] In step (1), the calcination temperature is 500-600° C., the calcination time is 4-8 hours, the pH value of the acid solution is 1-4, and the particle size of the pretreated FCC waste catalyst powder is not less than 200 meshes.
[0011] The molecular sieve-based catalyst contains one or more of ZSM-5 molecular sieve, ZSM-35 molecular sieve, SSZ-13 molecular sieve, SSZ-39 molecular sieve, SAPO-11 molecular sieve, SAPO-34 molecular sieve, SAPO-47 molecular sieve, Y-type molecular sieve, Beta molecular sieve, KFI type molecular sieve, and mordenite (MOR), and the molar ratio of silicon dioxide to aluminum oxide of the molecular sieve is 2 to 300: 1. The metal element contained in the molecular sieve-based catalyst is one or more of iron, copper, manganese, cerium, lanthanum, rhodium, ruthenium, palladium, and osmium, and the content of the metal element is 0.1 to 10.0wt%.
[0012] The organic binder is one or more of sodium carboxymethyl cellulose, sodium hydroxypropyl cellulose, polyethylene glycol, polyethylene oxide, sodium polyacrylate and phenolic resin.
[0013] The extrusion aid is one or more of flour, starch, sesbania powder, ethanolamine or sodium stearate.
[0014] The main length distribution of the glass fiber is 1.0-10.0 mm.
[0015] The structure manufacturing agent is a water-soluble polymer fiber, including one or more of water-soluble polyvinyl alcohol fiber, water-soluble seaweed fiber, and water-soluble carboxymethyl cellulose fiber. If it is in the form of a strip, specifically, the length is required to be 0.2 mm to 3.0 mm, the diameter is required to be 10 μm to 100 μm, and the length is adjusted according to the thickness of the honeycomb wall to achieve the purpose of directly penetrating the inner wall; if it is spherical, the mesh number is required to be not less than 200 meshes.
[0016] The pore-forming agent is plant fiber particles, including one or more of straw, rice husk, sawdust, wood chips, and bamboo chips, and the particle size is not less than 200 meshes.
[0017] The inorganic binder is one or more of silica sol, water glass, pseudo-boehmite or alumina sol.
[0018] The acid solution is an organic acid solution and an inorganic acid solution, the organic acid includes one or more of citric acid, tartaric acid, malic acid, oxalic acid, and lactic acid; the inorganic acid includes one or more of hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, and boric acid. The concentration of the organic acid solution and the inorganic acid aqueous solution is 5 to 20 wt%.
[0019] The moisturizing agent is one or more of glycerin, tung oil and peanut oil.
[0020] The water is one or more of deionized water, pure water and mineral water.
[0021] The mass ratio of each raw material is: FCC waste catalyst: molecular sieve: organic binder: extrusion aid: glass fiber: structure manufacturing agent: pore former: inorganic binder: organic acid: inorganic acid: humectant: water = 45-100: 1-35: 1-5: 1-8: 1-5: 10-50: 1-20: 3-8: 1-5: 1-5: 3-10: 10-25.
[0022] In step (1), the dry mixing and kneading steps are as follows: the molecular sieve-based catalyst and the pore-forming agent are mixed evenly to obtain powder A; the pretreated FCC waste catalyst powder is mixed evenly with the structure-forming agent and the glass fiber to obtain powder B; then the powder A, powder B, an extrusion aid and an organic binder are mixed evenly, and then an inorganic binder, an inorganic acid, an organic acid, a humectant and water are added for bonding.
[0023] The number of times of mud kneading is 2 to 3 times; the aging time is 1 to 10 days; the extrusion molding is a double-screw extrusion, which is carried out in conjunction with molds of different shapes, and the wall thickness adjustment range is 0.5 to 3.0 mm; the pre-drying is to pre-remove 5wt% of the moisture of the material; the drying method is a temperature and humidity coordinated cross-control method, that is, controlling the humidity and temperature curves to cross, and coordinated drying and dehydration; the calcination method adopts a low-rate platform heating method, and calcination is carried out in a closed muffle furnace.
[0024] The structured water-soluble method is to soak the pre-dried material in water at 20-90°C for 0.5-2.0h, and then rinse it with water at 20-90°C for 2-3 times (the water temperature in this step is set according to the dissolution temperature of the structure-making agent);
[0025] Furthermore, the drying method is: temperature and humidity are coordinated and cross-controlled, the temperature is controlled at 25-100°C, and the humidity is controlled at 5%-95%. Preferably, during the drying process, the temperature is first controlled at 25°C and the humidity is controlled at 80%; then the temperature is controlled at 40°C and the humidity is controlled at 60%; then the temperature is controlled at 60°C and the humidity is controlled at 40%; then the temperature is controlled at 80°C and the humidity is controlled at 10%. This method is conducive to controlling the drying rate and reducing cracking.
[0026] Furthermore, the calcination method is: the starting temperature is greater than 80°C, then the temperature is increased at a rate of 0.5-2°C / min, and when the temperature reaches 180-400°C, debinding is performed for 2-3 hours, and then the temperature is continued to be increased to 550-800°C and calcined for 6-12 hours.
[0027] Compared with the prior art, the advantages of the present invention are:
[0028] 1. The present invention uses FCC waste catalyst as a carrier, molecular sieve catalyst as an active component, adopts extrusion molding technology, and uses a water-soluble structure-making agent to structurally adjust the prepared catalyst to increase the activity accessibility.
[0029] 2. The present invention makes appropriate adjustments in the powder mixing step, premixes the pore former with the molecular sieve-based catalyst, premixes the structure-making agent with the FCC waste catalyst carrier, makes sufficient adjustments in the structural pores, and achieves the outer layer coating of the molecular sieve catalyst by adjusting the addition sequence, thereby increasing the active accessibility of the internal molecular sieve catalyst and effectively avoiding the pore blocking phenomenon of the molecular sieve catalyst caused by the addition of a binder.
[0030] 3. The present invention can realize the effective recycling of FCC waste catalysts, reduce the cost of solid waste treatment and the cost of preparing denitrification catalysts, complete high-value recycling, and enable the economical production of molecular sieve-based honeycomb monolithic denitrification catalysts, which has good industrial application prospects. DETAILED DESCRIPTION
[0031] The present invention is further described below in conjunction with specific examples, which are intended to illustrate the implementation scheme and features of the present invention in detail and should not be construed as any limitation of the present invention.
[0032] The FeCu-ZSM-5, FeCu-SSZ-13, Fe-MOR, and Fe-ZSM-5 molecular sieves in the examples are high-performance denitration molecular sieve catalysts synthesized in situ by a one-pot method, and are metal-modified molecular sieve catalysts. The addition of Fe can ensure the catalytic activity in the high-temperature stage, and the introduction of Cu is conducive to widening the temperature window in the low-temperature stage.
[0033] Example 1
[0034] A method for preparing a molecular sieve-based honeycomb denitration catalyst using FCC waste catalyst as a carrier comprises the following steps:
[0035] The following components were weighed in parts by mass: 45 parts of FCC waste catalyst, 40 parts of FeCu-SSZ-13 molecular sieve, 2 parts of sodium carboxymethyl cellulose, 6 parts of sesbania powder, 1 part of glass fiber (aspect ratio 2-4:1), 20 parts of water-soluble polyvinyl alcohol bundled fibers, 10 parts of sawdust, 8 parts of silica sol, 1 part of lactic acid, 1 part of nitric acid, 9 parts of glycerol, and 25 parts of deionized water.
[0036] 1) Take the FCC waste catalyst, roast it at 600°C for 8h to remove organic matter, then crush it to a particle size of not less than 200 mesh, add it into a dilute sulfuric acid solution (pH=2) and soak and stir for 5h, filter and take the filter cake, dry it at 90°C, roast it at 600°C for 5h, and crush it to a particle size of not less than 200 mesh to obtain a pretreated FCC waste catalyst powder;
[0037] 2) adding FeCu-SSZ-13 molecular sieve and sawdust into a mixer and mixing them evenly to obtain powder A;
[0038] The pretreated FCC waste catalyst powder, water-soluble polyvinyl alcohol fiber and glass fiber are added into a mixer and mixed evenly to obtain powder B;
[0039] Add powder A, powder B, sesbania powder and sodium carboxymethyl cellulose into a mixer and mix them evenly to obtain a uniform dry material;
[0040] Then add silica sol, nitric acid, lactic acid, glycerin and deionized water and knead;
[0041] 3) Repeat the kneaded clay for 3 times;
[0042] 4) Seal the clay with plastic wrap and place it in a dry and cool place to age for 24 hours;
[0043] 5) Put the prepared clay into a molding machine for extrusion molding;
[0044] 6) The formed honeycomb was pre-dried to remove 5 wt% of the total mass of water, and then placed in 100° C. boiling water to remove the water-soluble polyvinyl alcohol fibers. After soaking for 10 hours, the honeycomb was taken out and rinsed with 60° C. water for 3 times.
[0045] 7) Dry the rinsed material, and the drying curve is as follows: temperature 30°C, humidity 70%, drying for 10 hours; temperature 50°C, humidity 60%, drying for 5 hours; temperature 70°C, humidity 30%, drying for 3 hours; finally transfer to a common oven at 100°C and dry for 3 hours.
[0046] 8) The dried material is placed in a muffle furnace for calcination. The sintering curve is as follows: the temperature is raised from 100°C, the temperature is raised by 0.5°C per minute, the temperature is raised to 200°C for debinding for 3 hours, the temperature is further raised to 400°C for 2 hours, and the temperature is further raised to 600°C for 10 hours to obtain a molecular sieve-based honeycomb denitrification catalyst.
[0047] The prepared molecular sieve-based honeycomb denitrification catalyst was placed in the overall catalyst evaluation device to simulate the flue gas component N 2 NH 3 , H 2 O, NO, O 2 Conduct small sample evaluation and maintain airspeed at 5000h -1 , [NO] = [NH 3 ]=500ppm,[O 2 ]=5%,H 2 O=5%, the NO concentration at the inlet and outlet was detected respectively, and the denitration efficiency of the catalyst was calculated. The results are shown in Table 1.
[0048] Example 2
[0049] A method for preparing a molecular sieve-based honeycomb denitration catalyst using FCC waste catalyst as a carrier comprises the following steps:
[0050] The following components were weighed in parts by mass: 25 parts of FCC waste catalyst, 60 parts of FeCu-ZSM-5 molecular sieve, 2 parts of sodium carboxymethyl cellulose, 7 parts of sesbania powder, 1 part of glass fiber (aspect ratio 2-4:1), 25 parts of water-soluble polyvinyl alcohol fiber, 10 parts of bamboo powder, 5 parts of pseudo-boehmite, 1 part of lactic acid, 1 part of nitric acid, 9 parts of glycerol, and 40 parts of deionized water.
[0051] 1) Take the FCC waste catalyst, roast it at 600°C for 7h to remove organic matter, then crush it to a particle size of not less than 200 mesh, add it into a dilute sulfuric acid solution (pH=2) and soak and stir for 5h, take the filter cake after filtering, dry it at 80°C, roast it at 600°C for 5h, and crush it to a particle size of not less than 200 mesh to obtain the pretreated FCC waste catalyst.
[0052] 2) adding FeCu-ZSM-5 molecular sieve and bamboo powder into a mixer and mixing them evenly to obtain powder A;
[0053] The pretreated FCC waste catalyst, water-soluble polyvinyl alcohol fiber and glass fiber are added into a mixer and mixed evenly to obtain powder B;
[0054] Add powder A, powder B, sesbania powder and sodium carboxymethyl cellulose into a mixer and mix them evenly to obtain a uniform dry material;
[0055] Then add silica sol, nitric acid, lactic acid, glycerin and deionized water and knead;
[0056] 3) Repeat the kneaded clay for 2 to 3 times;
[0057] 4) Seal the clay with plastic wrap and place it in a dry and cool place to age for 40 hours;
[0058] 5) Put the kneaded clay into the molding machine for extrusion molding;
[0059] 6) The formed honeycomb was pre-dried to remove 5 wt% of the total mass of water, and then placed in 100° C. boiling water to remove the water-soluble polyvinyl alcohol fibers. After soaking for 10 hours, the honeycomb was taken out and rinsed with 60° C. water for 3 times.
[0060] 7) Dry the material, and the drying curve is as follows: temperature 30°C, humidity 70%, drying for 10 hours; temperature 50°C, humidity 60%, drying for 5 hours; temperature 70°C, humidity 30%, drying for 2 hours; finally, transfer to a common oven at 100°C and dry for 2 hours.
[0061] 8) The dried material is placed in a muffle furnace for calcination. The sintering curve is as follows: starting from 100°C, the temperature is increased by 0.5°C per minute, the temperature is increased to 200°C for debinding for 3 hours, the temperature is further increased to 400°C for 2 hours, and then the temperature is increased to 600°C for 8 hours to obtain a molecular sieve-based honeycomb denitrification catalyst.
[0062] The prepared molecular sieve-based honeycomb denitrification catalyst was placed in the overall catalyst evaluation device to simulate the flue gas component N 2 NH 3 , H 2 O, NO, O 2 Conduct small sample evaluation and maintain airspeed at 5000h -1 , [NO] = [NH 3 ]=500ppm,[O 2 ]=5%,H 2 O=5%, the NO concentration at the inlet and outlet was detected respectively, and the denitration efficiency of the catalyst was calculated. The results are shown in Table 1.
[0063] Example 3
[0064] A method for preparing a molecular sieve-based honeycomb denitration catalyst using FCC waste catalyst as a carrier comprises the following steps:
[0065] The following components were weighed in parts by mass: 55 parts of FCC waste catalyst, 30 parts of Fe-MOR molecular sieve, 6 parts of sodium carboxymethyl cellulose, 9 parts of sesbania powder, 1 part of glass fiber (aspect ratio 2-4:1), 25 parts of water-soluble polyvinyl alcohol fiber, 5 parts of straw, 5 parts of pseudo-boehmite, 1 part of malic acid, 4 parts of nitric acid, 7 parts of glycerol, and 17 parts of deionized water.
[0066] 1) The FCC waste catalyst was roasted at 600°C for 8 hours to remove organic matter, then crushed to a particle size of not less than 200 mesh, added to a dilute sulfuric acid solution (pH=3) and soaked and stirred for 5 hours, the filter cake was dried at 80°C, roasted at 600°C for 5 hours, and crushed to a particle size of not less than 200 mesh.
[0067] 2) Add Fe-MOR molecular sieve and straw into a mixer and mix them evenly to obtain powder A;
[0068] The pretreated FCC waste catalyst, water-soluble polyvinyl alcohol fiber and glass fiber are added into a mixer and mixed evenly to obtain powder B;
[0069] Add powder A, powder B, sesbania powder, pseudo-boehmite, and sodium carboxymethyl cellulose into a mixer and mix evenly to obtain a uniform dry material;
[0070] Then add malic acid, nitric acid, glycerin and deionized water and knead;
[0071] 3) Repeat the kneaded clay for 2 to 3 times;
[0072] 4) Seal the clay material with plastic wrap and place it in a dry and cool place for aging for 24 hours;
[0073] 5) Put the prepared clay into a molding machine for extrusion molding;
[0074] 6) The formed honeycomb is pre-dried, 5 wt% of water is removed, and then the honeycomb is placed in 60° C. water to remove water-soluble polyvinyl alcohol fibers. After soaking for 10 hours, the honeycomb is taken out and rinsed with 60° C. water for 3 times.
[0075] 7) The material is dried, and its drying curve is: temperature 30°C, humidity 80%, drying for 10 hours; temperature 40°C, humidity 70%, drying for 5 hours; temperature 70°C, humidity 30%, drying for 3 hours; finally transferred to a common oven at 100°C and dried for 3 hours.
[0076] 8) The material is placed in a muffle furnace for calcination. The sintering curve is as follows: starting from 100°C, the temperature is increased by 0.5°C per minute, the temperature is increased to 170°C for calcination and debinding for 2 hours, the temperature is further increased to 350°C and maintained for 2 hours, and then the temperature is increased to 550oC and maintained for 8 hours to obtain a molecular sieve-based honeycomb denitrification catalyst.
[0077] The prepared molecular sieve-based honeycomb denitrification catalyst was placed in the overall catalyst evaluation device to simulate the flue gas component N 2 NH 3 , H 2 O, NO, O 2 , maintain airspeed at 5000h -1 , [NO] = [NH 3 ]=500ppm,[O 2 ]=5%,H 2 O=5%, the NO concentration at the inlet and outlet was detected respectively, and the denitration efficiency of the catalyst was calculated. The results are shown in Table 1.
[0078] Example 4
[0079] A method for preparing a molecular sieve-based honeycomb denitration catalyst using FCC waste catalyst as a carrier comprises the following steps:
[0080] The following components were weighed in parts by mass: 60 parts of FCC waste catalyst, 25 parts of FeCu-ZSM-5 molecular sieve, 3 parts of sodium carboxymethyl cellulose, 5 parts of sesbania powder, 1 part of glass fiber (aspect ratio 2-4:1), 25 parts of water-soluble polyvinyl alcohol bundle fiber, 5 parts of sawdust, 4 parts of silica sol, 1 part of lactic acid, 1 part of nitric acid, 5 parts of glycerol, and 14 parts of deionized water.
[0081] 1) The FCC waste catalyst was roasted at 600°C for 8 hours to remove organic matter, then crushed to a particle size of not less than 200 mesh, added to a dilute sulfuric acid solution (pH=3) and soaked and stirred for 5 hours, the filter cake was dried at 80°C, roasted at 600°C for 5 hours, and crushed to a particle size of not less than 200 mesh.
[0082] 2) adding FeCu-ZSM-5 molecular sieve and sawdust into a mixer and mixing them evenly to obtain powder A;
[0083] (2) adding the pretreated FCC waste catalyst, water-soluble polyvinyl alcohol fiber, and glass fiber into a mixer and mixing them uniformly to obtain powder B;
[0084] Add powder A, powder B, sesbania powder, pseudo-boehmite, and sodium carboxymethyl cellulose into a mixer and mix evenly to obtain a uniform dry material;
[0085] Then add silica sol, lactic acid, nitric acid, glycerin and deionized water and knead;
[0086] 3) Repeat the kneaded clay for 2 to 3 times;
[0087] 4) Seal the clay with plastic wrap and place it in a dry and cool place for 48 hours;
[0088] 5) Put the prepared clay into a molding machine for extrusion molding;
[0089] 6) The formed honeycomb was pre-dried, 5 wt% of water was removed, and then placed in a 50° C. water bath to remove the water-soluble polyvinyl alcohol bundle fibers. After soaking for 10 hours, the honeycomb was taken out and rinsed with 60° C. water for 3 times.
[0090] 7) Dry the rinsed material, and the drying curve is as follows: temperature 30°C, humidity 80%, drying for 10 hours; temperature 50°C, humidity 60%, drying for 5 hours; temperature 70°C, humidity 30%, drying for 3 hours; finally transfer to an oven at 100°C and dry for 3 hours.
[0091] 8) The dried material is placed in a muffle furnace for calcination. The calcination curve is as follows: starting from 100°C, the temperature is increased by 0.5°C per minute, the temperature is increased to 230°C for calcination and debinding for 2 hours, the temperature is further increased to 420°C for calcination for 2 hours, and the temperature is increased to 650°C for calcination for 8 hours to obtain a molecular sieve-based honeycomb denitrification catalyst.
[0092] The prepared molecular sieve-based honeycomb denitrification catalyst was placed in the overall catalyst evaluation device to simulate the flue gas component N 2 NH 3 , H 2 O, NO, O 2 , maintain airspeed at 5000h -1 , [NO] = [NH3 ]=500ppm,[O 2 ]=5%,H 2 O=5%, the NO concentration at the inlet and outlet was detected respectively, and the denitration efficiency of the catalyst was calculated. The results are shown in Table 1.
[0093] Table 1 Denitration reaction evaluation results of the products of Examples 1 to 4
[0094]
[0095]
[0096] After experimental demonstration, the present invention selects FCC waste catalyst as a carrier, realizes the high-value utilization of solid waste, and the water-soluble polymer fiber effectively realizes the inner wall through structure, structurally adjusts the honeycomb body, and exposes the internal embedded molecular sieve catalyst; in addition, by adjusting the feeding sequence, the outer layer coating structure of the molecular sieve catalyst is realized, and the pore structure is increased. Compared with the traditional V-based catalyst, the present invention not only replaces the core catalyst, but also is more environmentally friendly in the recycling of solid waste, more in line with environmental protection and economy, and has practical application value.
Claims
1. A method for preparing a molecular sieve-based honeycomb denitration catalyst using FCC waste catalyst as a carrier, characterized in that: The following steps are involved: (1) The FCC waste catalyst is calcined to remove organic matter, crushed, etched with acid solution, filtered, dried, calcined, and crushed to obtain pretreated FCC waste catalyst powder; (2) Pretreated FCC waste catalyst powder, molecular sieve-based catalyst, structure-making agent, organic binder, inorganic binder, pore-forming agent, extrusion aid, glass fiber, acid solution, moisturizing agent and water are taken, and dry-mixed, kneaded, slurried, aged, extruded, pre-dried, structured in water, dried and calcined to obtain a molecular sieve-based honeycomb denitrification catalyst.
2. The method for preparing a molecular sieve-based honeycomb denitration catalyst using FCC waste catalyst as a carrier according to claim 1, characterized in that: In step (1), the calcination temperature is 500-600° C., the calcination time is 4-8 hours, the pH value of the acid solution is 1-4, and the particle size of the pretreated FCC waste catalyst powder is not less than 200 meshes.
3. The method for preparing a molecular sieve-based honeycomb denitration catalyst using FCC waste catalyst as a carrier according to claim 1, characterized in that: The molecular sieve-based catalyst contains one or more of ZSM-5 molecular sieve, ZSM-35 molecular sieve, SSZ-13 molecular sieve, SSZ-39 molecular sieve, SAPO-11 molecular sieve, SAPO-34 molecular sieve, SAPO-47 molecular sieve, Y-type molecular sieve, Beta molecular sieve, KFI type molecular sieve, and mordenite, and the molar ratio of silicon dioxide to aluminum oxide of the molecular sieve is 2 to 300:1; the metal element contained in the molecular sieve-based catalyst is one or more of iron, copper, manganese, cerium, lanthanum, rhodium, ruthenium, palladium, and osmium, and the content of the metal element is 0.1 to 10.0 wt%.
4. The method for preparing a molecular sieve-based honeycomb denitration catalyst using FCC waste catalyst as a carrier according to claim 1, characterized in that: The structure manufacturing agent is water-soluble polymer fiber, and the polymer fiber is one or more of polyvinyl alcohol fiber, seaweed fiber and carboxymethyl cellulose fiber.
5. The method for preparing a molecular sieve-based honeycomb denitration catalyst using FCC waste catalyst as a carrier according to claim 1, characterized in that: The organic binder is one or more of sodium carboxymethyl cellulose, sodium hydroxypropyl cellulose, polyethylene glycol, polyethylene oxide, sodium polyacrylate, and phenolic resin; The extrusion aid is one or more of flour, starch, sesbania powder, ethanolamine or sodium stearate; The pore-forming agent is plant fiber particles, and the plant fiber is one or more of straw, rice husk, sawdust, wood chips, and bamboo chips; The inorganic binder is one or more of silica sol, water glass, pseudo-boehmite or alumina sol; The acid solution is an organic acid solution and an inorganic acid solution, the organic acid is one or more of citric acid, tartaric acid, malic acid, oxalic acid, and lactic acid; the inorganic acid is one or more of hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, and boric acid; The moisturizing agent is one or more of glycerin, tung oil and peanut oil.
6. The method for preparing a molecular sieve-based honeycomb denitration catalyst using FCC waste catalyst as a carrier according to claim 1, characterized in that: The mass ratio of each raw material is: FCC waste catalyst: molecular sieve: organic binder: extrusion aid: glass fiber: structure manufacturing agent: pore former: inorganic binder: organic acid: inorganic acid: humectant: water = 45-100: 1-35: 1-5: 1-8: 1-5: 10-50: 1-20: 3-8: 1-5: 1-5: 3-10: 10-25.
7. The method for preparing a molecular sieve-based honeycomb denitration catalyst using FCC waste catalyst as a carrier according to claim 1, characterized in that: In step (1), the dry mixing and kneading steps are as follows: the molecular sieve-based catalyst and the pore-forming agent are mixed evenly to obtain powder A; the pretreated FCC waste catalyst powder is mixed evenly with the structure-forming agent and the glass fiber to obtain powder B; then the powder A, powder B, an extrusion aid and an organic binder are mixed evenly, and then an inorganic binder, an inorganic acid, an organic acid, a humectant and water are added for bonding.
8. The method for preparing a molecular sieve-based honeycomb denitration catalyst using FCC waste catalyst as a carrier according to claim 1, characterized in that: The structured water-soluble material is prepared by soaking the pre-dried material in water at 20 to 90° C. for 0.5 to 2.0 hours, and then flushing with water at 20 to 90° C. for 2 to 3 times.
9. The method for preparing a molecular sieve-based honeycomb denitration catalyst using FCC waste catalyst as a carrier according to claim 1, characterized in that: The drying method is temperature and humidity coordinated cross control, the temperature is controlled at 25-100°C, and the humidity is controlled at 5%-95%. The calcination method is as follows: the initial temperature is greater than 80°C, then the temperature is increased at a rate of 0.5-2°C / min, and when the temperature reaches 180-400°C, the binder is removed for 2-3 hours, and then the temperature is continued to be increased to 550-800°C and calcined for 6-12 hours.
10. Use of the molecular sieve-based honeycomb denitration catalyst obtained according to the preparation method according to any one of claims 1 to 9 in NH3-SCR reaction.
Citation Information
Patent Citations
A denitrification catalyst and its preparation method
CN109482222B
FCC waste catalyst treatment method, prepared adsorbent and application of adsorbent
CN115672262A
Denitration catalyst and preparation method thereof
CN109482222A
Low-temperature denitration catalyst carrier prepared from waste honeycomb TiO2 and FCC molecular sieves
CN109985670A
Low-temperature denitration catalyst synthesized by taking waste FCC (fluid catalytic cracking) catalyst as raw material and preparation method of low-temperature denitration catalyst
CN116689018A